Mobility Platform for Physically Challenged People using Wireless Sensor Network - Vidya, K; Aarthy, A (International Journal of Engineering and Technology, 2018)
The Primary objective of Automatic Railway Bridge System is to help the physically Challenged Passenger to move from one Platform to another. Crossing the railway track inside the railway station is very difficult. But it is quite difficult to the handicapped and aged persons to cross the railway track without the help of other. The proposed system uses the train time for opening and closing of bridges. This is done by wireless communication. Each train is connected with RF transceiver, which will send a data of arrival before it reaches the station platform. If the train leaves the platform, the automatically the mobile platform will be bridged between two platforms to build a path between them. This project is designed with arduino microcontroller. The arduino microcontroller gives the input  from the  RSSI and give command to the motor to run in order to change in the position of open and close the mobility rostrum